Service Quality Assessment using Servqual and Kano Models - Shanty Kusuma Dewi (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
This study aims to assess the quality of services by integrating Servqual and the Kano model. In this study, Servqual is used to determine the quality criteria that must be improved. At this method, the quality criteria are based on the gap between customer perceptions and expectations for the services they receive. Meanwhile, the Kano method is used to categorize service attributes that satisfy customer needs. Servqual integration and the Kano model were carried out by synchronizing the Servqual gap value and the Kano model grade. Assessment of service attributes obtained from both methods produces service attributes that will focus on management’s improvement to improve service quality. The results showed that the attribute criteria that must be prioritized were attributes that included attractive and one-dimensional categories, which had weak types at Servqual. Improvements in attributes in attractive and one-dimensional categories will improve service quality and increase customer satisfaction.